Content Characteristics and Customer Engagement: Their Impact on Brand Love, Self-Brand Connection, and Customer Brand Identification - Rimiyati, Hasnah; Hilmawan, Raden Ahmad Hilman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Social media has become an essential platform for companies to communicate with consumers and build stronger brand relationships. One of the key factors influencing consumer interaction on social media is the characteristics of the content shared by brands. This study aims to examine the influence of content characteristics—namely vividness, interactivity, novelty, consistency, and content type—on customer engagement and to investigate the effect of customer engagement on brand relationship outcomes, including brand love, self-brand connection, and customer brand identification. The study focuses on Instagram users who have interacted with the official Instagram account of Gojek Indonesia (@gojekindonesia). A quantitative research approach was employed, and data were collected from 168 respondents using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that interactivity, novelty, and content type have positive and significant effects on customer engagement, while vividness and consistency do not significantly influence engagement. Furthermore, customer engagement has a positive and significant effect on brand love, self-brand connection, and customer brand identification. These findings highlight the importance of developing interactive, innovative, and relevant social media content strategies to enhance consumer engagement and strengthen emotional and psychological relationships between consumers and brands.